1984
DOI: 10.1002/bit.260260812
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of enzymes in porous supports: Effects of support–enzyme solution contacting

Abstract: Proteins have been immobilized in porous support particles held in a fixed-bed reactor through which protein solution is continuously circulated. Changing the recirculation flow rate alters the observed immobilization kinetics and the maximum enzyme loading which can be achieved for glucose oxidase and glucoamylase on carbodiimide-treated activated carbon and for glucoamylase immobilized on CNBr-Sepharose 4B. Direct microscopic examination of FITC-labelled protein in sectioned Sepharose particles and indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The overall rate is often largest when the active site is located near the external surface rather than uniformly distributed (Wang and Varma, 1980). This conclusion has been demonstrated for immobilized enzyme catalysts as reported by Borchert and Buchholz (1979) and Dennis et al (1984). However, from a deactivation standpoint, the work by Corbett and Luss ( 1 974) has shown that uniformly loaded catalyst may be more stable than nonuniformly loaded catalyst.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The overall rate is often largest when the active site is located near the external surface rather than uniformly distributed (Wang and Varma, 1980). This conclusion has been demonstrated for immobilized enzyme catalysts as reported by Borchert and Buchholz (1979) and Dennis et al (1984). However, from a deactivation standpoint, the work by Corbett and Luss ( 1 974) has shown that uniformly loaded catalyst may be more stable than nonuniformly loaded catalyst.…”
Section: Discussionmentioning
confidence: 68%
“…Recently it was suggested by Dennis et al (1984) that restricted diffusion may cause nonuniform distribution of enzymes in porous supports. On the basis of this, a mathematical model has been formulated by Clark et al ( 1 985).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, it is not unity because of the main reaction. However, its initial location Xo can be found by matching equation (19) at zero time to the quasi-steady-state solution for Ab given in equation (13). We find (19) and (22) yields…”
Section: From Equation (17) One Obtainsmentioning
confidence: 97%
“…[41) Similarly, immobilized antibodies have been found to have reduced affinity and capacity (on a molar basis) for binding compared with soluble antibodies.l l l .4 s . 46 ) Reduced enzymatic activity has been attributed to phenomena such as immobilizing bond-induced conformational changes,[41.4 7 ) increased immobilized enzyme density, [48) and support/substrate ionic repulsion. [49) Immobilized antibodies have also been shown to have reduced capacity (on a per mole basis) at higher antibody concentrations and higher activation levels.…”
Section: Equilibrium Modelsmentioning
confidence: 99%